Laws of Collateral in Today's World in Islamic Perspective - Aqeel Akhtar; Fahad Ahmed Qureshi; Mubeen Butt (Shirkah: Journal of Economics and Business, 2018)
Taking from Pakistan State Bank case, this article initially elaborates and critically discusses collateral (in conventional term) and Islamic collateral (rahn). In conventional banking, collateral traditionally refers to secured lending (also known as asset-based lending). Since possession is pre-requisite for binding of the contract, the charge can be registered in this regard to the regulating authority. Third party charge registration in this regard will not be entertained until the debtor scrutinizes it with registration. We argue that it is allowed for a creditor to take one asset as collateral from two debtors and this asset will be considered from both debtors as rahn. Since one single asset is considered from both debtors, the creditor may hold the asset until his whole debt would be paid off. Although this research happens in Pakistan, the case of collateral and rahn can be academic precedence in Islamic global world.Â Â Keywords: collateral, rahn, Pakistan state-banking